Acute exacerbation of anti-Ha antibody-positive antisynthetase syndrome-associated interstitial lung disease: a case report - Yinying Li; Junyi Ke; Shu Huang; Shiya Lin; Siyu Lei; Hongchun Huang; Luxi Lei; Qinglan Li; Yuanlan Wu; Minchao Duan; Minchao Duan (Frontiers in Immunology, 2025)
BackgroundAnti-synthetase syndrome (ASS) is a rare autoimmune myopathy, frequently associated with interstitial lung disease, and is characterized by the presence of anti-aminoacyl tRNA synthetase (ARS) antibodies. However, there have been limited reports of cases exhibiting positive anti-Ha antibodies.MethodsThis study presents a retrospective analysis of the clinical data from a patient with an acute exacerbation of ASS who tested positive for anti-Ha antibodies.Case presentationThis patient initially presented with interstitial pneumonia. The initial anti-infective treatment was ineffective; however, symptoms improved following the addition of corticosteroids. Upon discontinuation of corticosteroids, the patient experienced a recurrence of cough, progressive worsening of dyspnea, and developed lower general weakness. Comprehensive autoantibody testing revealed positivity for anti-Ha antibodies, and MRI of the lower limbs indicated soft tissue edema. The patient was ultimately diagnosed with ASS with interstitial lung disease. Treatment with methylprednisolone pulse therapy, combined with cyclophosphamide, tacrolimus, tofacitinib citrate, and pirfenidone, led to an improvement in the patient’s condition, resulting in discharge. Post-discharge, the patient was maintained on regular oral prednisone, nintedanib, and tofacitinib. Follow-up to date has shown a stable condition, with resolution of pulmonary lesions observed upon re-examination.ConclusionAnti-Ha antibody is one of the specific antibodies associated with ASS, yet its positive rate remains exceedingly low. This case represents the first reported instance of an anti-Ha antibody-positive ASS in China. Misdiagnosis and missed diagnosis are prevalent in clinical practice, underscoring the importance of screening for autoantibodies when patients present with acute, unexplained interstitial lung changes and a poor response to anti-infective treatment. Furthermore, interstitial lung disease is the most common extra-muscular clinical manifestation observed in ASS patients. Differentiating between acute exacerbations of pulmonary infections and interstitial lung disease associated with rheumatic diseases poses a significant challenge, as both can occur concurrently. Therefore, during diagnosis and treatment, it is crucial to consider not only infections but also to identify the underlying causes of worsening lung lesions.